Urokinase-type plasminogen activator promotes N-cadherin-mediated synaptic recovery in the ischemic brain. Issue 9 (September 2021) - Diaz, Ariel; Merino, Paola; McCann, Patrick; Yepes, Manuel A; Quiceno, Laura G; Torre, Enrique; Tomkins, Amelia; Zhang, Xiaodong; Hales, Chadwick M; Tong, Frank C; Yepes, Manuel
Urokinase-type plasminogen activator (uPA) is a serine proteinase that catalyzes the generation of plasmin on the cell surface and activates cell signaling pathways that promote remodeling and repair. Neuronal cadherin (NCAD) is a transmembrane protein that in the mature brain mediates the formation of synaptic contacts in the II/III and V cortical layers. Our studies show that uPA is preferentially found in the II/III and V cortical laminae of the gyrencephalic cortex of the non-human primate. Furthermore, we found that in murine cerebral cortical neurons and induced pluripotent stem cell (iPSC)-derived neurons prepared from healthy human donors, most of this uPA is associated with pre-synaptic vesicles. Our in vivo experiments revealed that in both, the gyrencephalic cortex of the non-human primate and the lissecephalic murine brain, cerebral ischemia decreases the number of intact synaptic contacts and the expression of uPA and NCAD in a band of tissue surrounding the necrotic core. Additionally, our in vitro data show that uPA induces the synthesis of NCAD in cerebral cortical neurons, and in line with these observations, intravenous treatment with recombinant uPA three hours after the onset of cerebral ischemia induces NCAD-mediated repair of synaptic contacts in the area surrounding the necrotic core.